Optimization of a heavy-duty elevated thin shell structure - Azizah, Abdul Nassir; Min, Yee Hooi; Arthit, Petchsasithon; Syahrul Fithry, Senin (Prince of Songkla University, 2022)
Optimization means the mathematical determination of the optimal decisions out of diverse alternatives. Based on the preceding Finite Element Analysis (FEA), a proposed shell produced a maximum stress that exceeded the design value. To make the design feasible, an optimization was done to minimize the maximum stress by using the gradient method. The performance of the structure can be optimized to fulfil the design requirements with the optimum value of displacement to achieve the objective function. The results show that the optimum displacement is 8.8mm, which reduced the maximum stress by 99.94% from the initial level. Thus, optimization methods are important for new applications of shell structures to find their best parameters in the design stage.